WAYS TO IMPROVE PEDAGOGICAL LITERACY OF PARENTS - Eminjon Aliyevich Ergashev (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the importance of the level of pedagogical literacy of parents in effectively solving the tasks of raising teenagers in the modern family and the ways to increase the pedagogical literacy of parents.